2023
DOI: 10.1038/s41598-023-32971-0
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive lysosomal-metabolic signaling and neurodevelopmental deficits that precede Purkinje cell loss in a mouse model of Niemann-Pick Type-C disease

Abstract: Purkinje cell (PC) loss occurs at an early age in patients and animal models of Niemann-Pick Type C (NPC), a lysosomal storage disease caused by mutations in the Npc1 or Npc2 genes. Although degeneration of PCs occurs early in NPC, little is known about how NPC1 deficiency affects the postnatal development of PCs. Using the Npc1nmf164 mouse model, we found that NPC1 deficiency significantly affected the postnatal development of PC dendrites and synapses. The developing dendrites of Npc1nmf164 PCs were signific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…It has been suggested that an interplay between mitophagy and mitochondrial biogenesis is necessary to prevent pathological conditions associated with mitochondria dysfunction [ 30 , 31 ]. Accumulation of fragmented and damaged mitochondria has been found in Purkinje cells from NPC1 mutant mice and in vitro NPC1 deficient cellular models where lysosomal degradation is severely impaired [ 11 , 13 , 24 ]. In this study, NPC1 mutant fibroblasts were able to increase mitochondrial length after serum starvation and reintroduction of CM, suggesting that a potential increase in lysosomal activity induced by serum starvation enhanced the fusion or biogenesis of mitochondria when CM was reintroduced.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that an interplay between mitophagy and mitochondrial biogenesis is necessary to prevent pathological conditions associated with mitochondria dysfunction [ 30 , 31 ]. Accumulation of fragmented and damaged mitochondria has been found in Purkinje cells from NPC1 mutant mice and in vitro NPC1 deficient cellular models where lysosomal degradation is severely impaired [ 11 , 13 , 24 ]. In this study, NPC1 mutant fibroblasts were able to increase mitochondrial length after serum starvation and reintroduction of CM, suggesting that a potential increase in lysosomal activity induced by serum starvation enhanced the fusion or biogenesis of mitochondria when CM was reintroduced.…”
Section: Resultsmentioning
confidence: 99%
“…NPC1 deficiency leads to the early degeneration of neurons in Niemann-Pick Type C disease. Given that reduced levels and fragmentation of mitochondria are found in Purkinje cells (PCs) from Npc1 nmf164 mutant mice [ 11 ], we pursued to determine the effects of TH treatment in NPC1 mutant PCs. Cerebellar slices at postnatal day 10 (P10) from wild type (WT) and Npc1 nmf164 mutant mice were used for organotypic slice cultures, and after 4 days in vitro (DIV) were fixed and immunolabeled with calbindin (CALB) and PDHE1 antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations